Histomorphometry of Umbilical Cord and its Vessels in Pre- Eclampsia as Compared to Normal Pregnancies - Barnwal, Manisha; Rathi, SK; Chhabra, S; Nanda, S (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: To study and compare the morphometric alteration in the umbilical cord obtained from thirty normal pregnancies (Group-I) and thirty pre-eclamptic pregnancies (Group-II). Methods: Morphological changes in umbilical cords were examined on formalin fixed paraffin embedded section. Various parameters were measured by planimeter. Results: In pre-eclamptic group total vessel area, total vein area, total luminal area of vein, and wall thickness of arteries were increased, whereas jelly area and wall thickness of vein were decreased as compared to normal group. Conclusion: Increased umbilical arterial thickness, decreased umbilical vein wall thickness and increased luminal area of vein which could be a predictor of intrauterine growth retardation in term pre-eclamptic patients. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 28-32 DOI: http://dx.doi.org/10.3126/njog.v7i1.8832